P+q/pq к знаменателю p²q3/a+3 к знаменателю 2a+62/b-1 к знаменателю 4b-4

0 голосов
32 просмотров

P+q/pq к знаменателю p²q
3/a+3 к знаменателю 2a+6
2/b-1 к знаменателю 4b-4


Алгебра (92 баллов) | 32 просмотров
0

и что нужно сделать?

0

привести дроб

Дано ответов: 2
0 голосов
Правильный ответ

Решите задачу:

\frac{p+q}{pq} = \frac{(p+q)*p}{pq*p} = \frac{p(p+q)}{p^2q}

\frac{3}{a+3} = \frac{3*2}{(a+3)*2} = \frac{6}{2a+6}

\frac{2}{b-1} = \frac{2*4}{(b-1)*4} = \frac{8}{4b-4}
(62.7k баллов)
0 голосов

Решите задачу:

\frac{p+q}{pq}=\frac{p(p+q)}{p^2q}\\\\\frac{3}{a+3}=\frac{2\cdot 3}{2(a+4)}=\frac{6}{2a+6}\\\\\frac{2}{b-1}=\frac{4\cdot 2}{4(b-1)}=\frac{8}{4b-4}
(835k баллов)